GERAKAN BERSIH PANTAI SEBAGAI UPAYA MENGURANGI SAMPAH PADA LINGKUNGAN PESISIR DI PANTAI ELAK-ELAK, SEKOTONG - Diniariwisan, Damai; Affandi, Rangga Idris; Rahmadani, Thoy Batun Citra; Diamahesa, Wastu Ayu; Sumsanto, Muhammad; Scabra, Andre Rachmat (Universitas Mataram, 2024)
Waste is the result of discarded unused materials which generally come from human activities. The rapid development in the tourism sector, especially at Elak-elak Beach, Sekotong, West Nusa Tenggara, has made the waste problem quite crucial. The aim of this beach clean movement activity is a form of community service to reduce the amount of rubbish on Elak-elak beach, so that it can preserve the environment and increase its attraction for tourists. The method used begins with location observations followed by the implementation of beach clean-up activities. The total number of participants who participated in this activity was 116 people. This activity succeeded in collecting various kinds of waste, ranging from organic and inorganic waste, where organic waste consisted of leaves and tree twigs. Meanwhile, inorganic waste is dominated by plastic waste such as cans, mineral water bottles, straws, plastic food wrap and styrofoam. A survey was also conducted on several tourist visitors regarding waste, where basically the visitors had a good understanding of waste. The beach clean movement activity ends with collecting the resulting rubbish which will then be transported to the landfill. The beach clean movement is a form of concern for environmental management. It is hoped that the activity can help raise awareness and raise people's sense of concern for the cleanliness and sustainability of the environment, especially beaches. Further service activities can be carried out by providing assistance and training to coastal communities.